PERKEMBANGAN E-COMMERCE DARI MASA KE MASA: SEJARAH, TREN, DAN FAKTOR-FAKTOR YANG MEMENGARUHI KEMAJUAN TRANSAKSI ONLINE DI INDONESIA - Fandiyanto, Randika; Febriyanti, Dela Ayu; Triana, Suci; Luthfiaturahmah, Luthfiaturahmah; Amelia, Ana; Paramita, Dwi; Kamila, Aminatus Taniatul; Andrian, Mohammad Vicry (Fakultas Ekonomi dan Bisnis, 2025)
Electronic commerce (e-commerce) has become an important part of the digital transformation of the Indonesian economy. Advances in information technology, increasingly widespread internet penetration, and changes in consumer behavior have driven the rapid growth of this sector in the last two decades. This study aims to examine the development of e-commerce in Indonesia from a historical perspective, marketplace usage trends, and factors that influence the growth of online transactions. The research method used is descriptive qualitative with a literature study approach, through the collection and analysis of secondary data from various trusted sources such as scientific journals, industry reports, and government publications. The results of the study show that since the emergence of Tokobagus.com in 2005 to the presence of large platforms such as Shopee and Tokopedia, the e-commerce industry in Indonesia has experienced significant growth. Shopee dominates the market with the highest monthly visits, while Tokopedia, Lazada, and Bukalapak have experienced a decline in traffic. The main factors driving this growth include the digitalization of MSMEs, promotion through social media, and the increasing adoption of digital technology by the community. Cooperation is needed between the government, community, and academics in creating an inclusive, adaptive, and sustainable e-commerce ecosystem to support the digital economic transformation in Indonesia. Keywords: E-Commerce, Marketplace, Online Transactions, MSMEs, Indonesia